Role of Abia State Public Library Board in Continuing Education - Onyenachi, Joy C.; Ogbuagu, Ozioma Prudent; Uchendu, Ogechukwu Salome (Communicate: Journal of Library and Information Science, 2022)
The paper investigated The Role of Abia State Public Library Board Services in Adult Continuing Education Survey method was used as research design. Instruments for data collection are observation checklist and questionnaire. The population is 150 staff made up of 15 librarians and 17 library offices (Para-Professionals) and 102 support staff. No sampling because the population is manageable. Findings from the study show the following: collection of Abia State Library Board as at 2021/2022 holding are Fictions, Non-fictions, Textbooks, Journals, Pictures, Reference materials, Television sets, and Braille materials; The government should ensure that adult citizens are properly provided for as to gain from continuing education; Adequately staffed with quality and competent personnel; Well funding by the government for provision of information; Automated for information delivery in this electronic age; and constantly electrified to make the learning space properly lit and cooling from fan/air conditioner.